Desempenho agronômico e industrial de linhagens endogâmicas de milho (Zea mays L.) em duas safras na região de chapadões - ELBER VINICIUS MARTINS SILVA (2024)
The genetic improvement of corn (Zea mays L) has evolved significantly over the years, which has allowed food security throughout this period and boosted part of the world economy, with increased productivity. Much of the increase in production and nutritional improvements in corn is due to genetic improvement, in which obtaining superior hybrids is directly involved with the identification of more promising lines, for the formation of simple hybrids that, in general, are more productive. Faced with few studies to develop specific hybrids for the region, the objective of the work was to evaluate inbred corn lines and identify productive lines with good industrial starch and carbohydrate qualities, with potential for the formation of simple hybrids for the Chapadões region. The experiments were carried out during the second harvest of 2023 (environment 1) and the first harvest of 2024 (environment 2). The design used was augmented blocks containing 60 inbred lines of corn. The agronomic variables evaluated in three plants per plot were: plant height (ALT); culm diameter (DC); tang diameter (DE); number of rows per ear (NFE) and productivity (PROD). Lines 5,6,10,16,17,20,23,31,34 and 60 showed promise for future crossings, as they presented the highest averages in agronomic and industrial characteristics in both environments. Keywords: Lineage. Carbohydrate. Productivity. Starch.